Mechanosensitive Piezo1 channel: an emerging target in demyelination disease - Zhang, Yuxi; Yang, Xiaoke; Deng, Simin; Wang, Chenxu; Hu, Jialing; Lan, Qinghai (Frontiers in Cellular Neuroscience, 2025)
Many physiological processes in the human body are initiated by mechanical signals, which are transmitted via ion channels. Piezo-type mechanosensitive ion channel component 1 (Piezo1) is a protein highly expressed in the brain, playing a critical role in sensing changes in the mechanical microenvironment. Extensive research has demonstrated that Piezo1 is an essential component for generating currents in mechanically activated cation channels. It is involved in several key processes in the nervous system, including neuronal development and differentiation, nerve regeneration, axon guidance, and myelination. Demyelinating diseases, characterized by the loss of nerve myelin sheaths, occur in the central or peripheral nervous system. These diseases are clinically challenging due to their diverse etiologies, multiple types, poor prognosis, and lack of definitive cures. This article aims to review the current research on the role of Piezo1 in myelination and its involvement in demyelinating diseases, as well as to explore the potential of targeting Piezo1 for therapeutic interventions in such conditions.